DETEKSI PENYAKIT VIRAL PADA UDANG VANNAMEI (Litopennaeus vannamei) DENGAN METODE Polymerase Chain Reaction (PCR) - Bambang Hanggono; Muhammad Junaidi (Faculty of Science and Technology University Ibrahimy, 2015)
This study aimed to determine the clinical symptoms of the virus vannamei shrimp and to know the diagnosis techniques for the detection of TSV, IHHNV, WSSV at IMNV and vannamei shrimp by PCR. Materials used in the study were 180 samples of vannamei shrimp larvae consisted of 75 samples, 25 samples naupli, 60 samples and 20 samples tokolan swimming leg. This study uses survey, primary data collected by observation, interview documentation, and active participation. While the secondary data collected through the study of literature. Data already collected then analyzed descriptively. The analysis showed that the clinical symptoms of the disease caused by the virus is contained white spots on a pale yellowish kultikultula and less appetite for shrimp IHHNV. As for the body IMNV virus looks like a pale shrimp boiled shrimp. Process (PCR) to detect the presence of infection firus consists of extraction, amplification, elektroforosis, and documentation. PCR test results on 180 samples of shrimp is 5 WSSV infected samples, 3 samples infected with IHHNV, 11 infected samples IMNV and the rest are not infected with the virus.